Immunotherapy With 5, 15-DPP Mediates Macrophage M1 Polarization and Modulates Subsequent Mycobacterium tuberculosis Infectivity in rBCG30 Immunized Mice - Ahmad, Faraz; Umar, Mohd. Saad; Khan, Nazoora; Jamal, Fauzia; Gupta, Pushpa; Zubair, Swaleha; Gupta, Umesh Datta; Owais, Mohammad (Frontiers in Immunology, 2021)
Tuberculosis (TB) is a significant and continuing problem worldwide, with a death toll of around 1.5 million human lives annually. BCG, the only vaccine against TB, offers a varied degree of protection among human subjects in different regions and races of the world. The majority of the population living near the tropics carries a varying degree of tolerance against BCG due to the widespread prevalence of non-tuberculous mycobacteria (NTM). Interestingly, ≈90% of the Mycobacterium tuberculosis (Mtb) infected population restrain the bacilli on its own, which strengthens the notion of empowering the host immune system to advance the protective efficacy of existing mycobacterial vaccines. In general, Mtb modulates IL-10/STAT3 signaling to skew host mononuclear phagocytes toward an alternatively activated, anti-inflammatory state that helps it thrive against hostile immune advances. We hypothesized that modulating the IL-10/STAT3 driven anti-inflammatory effects in mononuclear cells may improve the prophylactic ability of TB vaccines. This study investigated the immunotherapeutic ability of a porphyrin based small molecule inhibitor of IL-10/STAT3 axis, 5, 15-diphenyl porphyrin (DPP), in improving anti-TB immunity offered by second generation recombinant BCG30 (rBCG30-ARMF-II®) vaccine in mice. The DPP therapy potentiated vaccine induced anti-TB immunity by down-modulating anti-inflammatory responses, while simultaneously up-regulating pro-inflammatory immune effector responses in the immunized host. The employed DPP based immunotherapy led to the predominant activation/proliferation of pro-inflammatory monocytes/macrophages/DCs, the concerted expansion of CD4+/CD8+ effector and central memory T cells, alongside balanced Th17 and Treg cell amplification, and conferred augmented resistance to aerosol Mtb challenge in rBCG30 immunized BALB/c mice.